ANALISIS DEBIT ALIRAN AIR TANAH PADA KAWASAN GAMBUT TROPIS DI SEKITAR SALURAN BERSEKAT DESA KALAMPANGAN - Donny Heryadi; Haiki Mart Yupi; I Made Kamiana (Program Studi Teknik Sipil, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2026)
Tropical peatlands are an ecosystem crucial for storing carbon and water, with characteristics that make them vulnerable to changes caused by agricultural land, road infrastructure, canal blocking, and other activities. These changes will affect the water balance. One of the parameters of the water balance is groundwater discharge (Q). This research aims to analyze the Q value, groundwater level (TMAT) hydrograph, and water level in the canal (TMAS) hydrograph around blocking channels in tropical peatlands in Kalampangan Village. This research was conducted by measuring fluctuations in TMAT and TMAS. Measure the hydraulic conductivity (K) using the slug test method, with a modified instrument consisting of a measuring float and its base, then test at P2 and P3. Measurements of the wet cross-sectional area and calculations of the hydraulic gradient were also performed to obtain Q using Darcy's Law. For the hydrograph, connect Q, TMAT, and TMAS data to time. The analysis results show that the Q value ranges from 1,47×10-6 to 1,60×10-6 m3/s, with an average of 1,53×10-6 m3/s. Based on the hydrograph, TMAT is influenced by TMAS, and Q flows from tropical peatlands to channels (outflow) because TMAS is lower than TMAT.